Organizational Culture, Strategy Implementation and Commercial Bank Performance in Zimbabwe - Goromonzi, Winfred O. (International Review of Management and Marketing, 2016)
The study investigates the impact of organizational culture and strategy implementation on commercial bank performance in Zimbabwe. Using a four factor, six dimensional organizational culture index and an eight dimensional strategy implementation index to statistically measure culture and strategy implementation impact, the study employs Ordinary Least Regression method to quantify and econometrically model the impact of the two variables on commercial bank performance. Data collection was achieved through questionnaire administration. The results of the study show that culture and strategy implementation have a statistically significant and positive impact on commercial bank performance. For banks which are regarded as performing (both average and high), organizational culture has strong positive effect on their performance while for smaller and poor performing banks, the effect of organizational culture was nearly neutral. Strategy implementation was also found to have strong positive effect in high performing banks and between neutral to negative effect in non-performing banks. The study concludes that the dynamic environment under which banks operate makes the impact of intangible resources differ across institutions. Based on the results of this study, it is recommended that leadership of commercial banks need to invest in creating a defining culture in banks and effective strategy implementation techniques. Utilising such attributes remains a major determinant of commercial bank performance in Zimbabwe. Keywords: Organizational culture, strategy implementation, organizational performance JEL Classifications: C39, L20